HUBUNGAN BEBAN KERJA FISIK DENGAN KELUHAN MUSKULOSKELETAL PADA PERAWAT DI RUANG LELY 1 DAN 2 RSUD BULELENG - Luh Dea Pratiwi; I Kadek Saputra; Meril Valentine Manangkot (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
Nurses are the most health professional in hospital that have to handle and treat patients for 24 hours and give nursing care using manual material handling. Manual material handling has risks creating a physical workload that is characterized by pain in muscle area called musculoskeletal disorders. This study aimed to determine the correlation of physical workload and musculoskeletal disorders among nurses in Lely 1 and 2 wards of Buleleng Hospital. This study was descriptive correlational with a cross sectional study design. Sample in this study was 25 respondents who were selected by probability sampling method with total sampling. The research instrument that used in this study was cardiovascular load using ten pulse method and Nordic Body Map. The correlation of physical workload and musculoskeletal disorders among nurses was analyzed using Pearson Product Moment because the data were normally distributed. The results show that most of respondents has very mild physical workload categories (84%) and low category musculoskeletal disorders (84%). Pearson Product Moment test shows a significant result with p-value=0,000, r = 0,806. In conclusion, there is a positive relationship between physical workload and musculoskeletal disorders among nurses in the Lely 1 and 2 wards of Buleleng Hospital. Based on the results of this study, it is recommended to apply ergonomic attitudes according to the procedure of nursing care